Feasibility Study of Using Huffman Code Calculator in Learning Achievement of Data Compression - Zulhelman Hanafi; Mohamad Fathurahman; Endang Saepudin (Spektral, 2021)
In the world of education there is already a curriculum that must be carried out with learning outcomes that must be achieved by students, as well as lecturers who also have duties as facilitators in these achievements. With the Learning Outcomes, it makes students have the ability or competence in accordance with the requirements to meet the predefined study program profiles. One of the competencies that graduates of the Broadband Multimedia field must achieve is in the field of data processing including data compression. The most widely used data compression technique is the Huffman code. Some research on the Huffman code has been done a lot, and someone has made the Calculator application. The calculator is used to determine the code for each character. The code for each character is not fixed, depending on the frequency of appearance in a text. The more often the character appears, the shorter the code. In this study, it has proven that the feasibility of the Huffman Calculator as a tool for Learning Outcomes can be done where data compression with language variables, in this case English and Bahasa Indonesia to the compression ratio, produces the same compression ratio, which ranges from 1.51 to 1.64 for Bahasa Indonesia while English is 1.56 to 1.83, with the average entropy for English 4.35 and Bahasa Indonesia 4.41.   Keywords: competence , data compression,  huffman code, learning outcomes.